EFFECTS OF LOW-LOAD RESISTANCE TRAINING UNDER MODERATE HYPOXIA ON MUSCLE STRENGTH AND POWER IN FEMALE COLLEGIATE TEAM SPORT ATHLETES - Muangritdech, Nattha; Namboonlue, Chaiyawat (Journal of Sports Science and Health, 2021)
Purpose : The purpose of this study was to examine and compare the effects of lowload resistance training under moderate hypoxia on muscle strength and power in female collegiate team sport athletes. Methods : Nineteen female sport athletes, aged 19-23 years old, from Ubon Ratchathani Rajabhat University were recruited to participate in this study. The participants were randomly divided into 2 resistance training groups; an experimental group (Hypoxic group; F1O2 = 15.8%, n = 10) and a control group (Normoxic group; F1O2 = 20.9%, n = 9). Both groups completed resistance training, consisted of 3 sets of 15 repetitions of knee extensions and knee flexions, separated by 1-minute rest between sets, 3 days a week for 5 consecutive weeks. Body composition, maximum muscle strength, muscle endurance, muscle power and maximum oxygen uptake were measured before and after 5-week of resistance training. Results : After training, maximum muscle strength in knee flexion and vertical jump were significantly increased p < 0.05 in the hypoxic group (20.88% and 3.85%) compared with normoxic group (8.56% and 1.67%). Moreover, hypoxic group showed substantially improvement in fat mass and fat-free mass (-3.48% and 2.34%, p < 0.05) after training compared to their baselines, with no difference detected between groups (p > 0.05). Conclusion : This study showed a low-load resistance training (50% 1RM) with moderatedose hypoxic condition (F1O2 = 15.8%) induced a significant increase in muscle strength and power. Therefore, this training program could be used as an alternative strategy for improving muscular performance without causing any injury in team sport athletes.